Covid-19 Prevention Practices and Associated Factors among Workers in Yirgalem Agro-Industry Park, Sidama Regional State, Ethiopia: A Cross Sectional Study (International Journal of Occupational Safety and Health, 2023)
Introduction: The COVID-19 outbreak resulted in millions of cases and deaths with an incredible pace of spread. It has been a global public health crisis since December 2019. Though the work behaviors of some organizations can facilitate more ways for the mode of transmission, the potential work areas for the risk of infection are not identified yet. Designing intervention strategies based on the risky assessment findings of a specific population or organization is better. The problem is more significant in developing countries. This study aimed to assess the prevention practices and associated factors of COVID-19 among workers in Yirgalem Agro-Industrial Park, Sidama Regional State; Ethiopia, 2020Methods: Cross-sectional study was conducted from June 15th to August 15th, 2020. Yirgalem Agro-Industrial Park had 233 workers during the study period and data were collected from all of them. Collected data were entered into Epi Data 3.1 and exported to SPSS 22 for analysis. Factors associated with the practice of prevention were then analyzed.Results: Among the respondents, 91.8%, 75.1%, and 48.9% had good knowledge, positive attitudes, and good practice toward COVID-19 prevention strategies respectively. Multivariate regression revealed that age, spiritual or sin, training, knowledge, attitude, opposition to wearing, ordinary residents, and hoping leaders can win against COVID-19 were predicted practices of COVID-19 prevention strategiesConclusion: The practice of COVID-19 prevention strategies was so poor and needed adequate attention. Age, spiritual/sin as a cause, prior training, knowledge, attitude, opposing mask-wearing, and belief in whether to defeat COVID-19 or not were identified as the predictors. It is so important to revamp the current practices and assure the implementation of the standard as expected.